Unraveling the Relevance of Tissue‐Specific Decellularized Extracellular Matrix Hydrogels for Vocal Fold Regenerative Biomaterials: A Comprehensive Proteomic and In Vitro Study. Issue 4 (31st January 2023) - Brown, Mika; Zhu, Shirley; Taylor, Lorne; Tabrizian, Maryam; Li-Jessen, Nicole Y. K.
Abstract : Decellularized extracellular matrix (dECM) is a promising material for tissue engineering applications. Tissue‐specific dECM is seen as a favorable material that recapitulates a native‐like microenvironment for cellular remodeling. However, the minute quantity of dECM derivable from small organs like the vocal fold (VF) hampers manufacturing scalability. Small intestinal submucosa (SIS), a commercial product with proven regenerative capacity, may be a viable option for VF applications. This study aims to compare SIS and VF dECM hydrogels with respect to protein content and functionality using mass spectrometry‐based proteomics and in vitro studies. Proteomic analysis reveals that VF and SIS dECM share 75% of core matrisome proteins. Although VF dECM proteins have greater overlap with native VF, SIS dECM shows less cross‐sample variability. Following decellularization, significant reductions of soluble collagen (61%), elastin (81%), and hyaluronan (44%) are noted in VF dECM. SIS dECM contains comparable elastin and hyaluronan but 67% greater soluble collagen than VF dECM. Cells deposit more neo‐collagen on SIS than VF‐dECM hydrogels, but comparable neo‐elastin (≈50 μg scaffold −1 ) and neo‐hyaluronan (≈6 μg scaffold −1 ). Overall, SIS dECM possesses a reasonably similar proteomic profile and regenerative capacity to VF dECM. SIS dECM is a promising alternative for dECM‐derived biomaterials for VF regeneration. Abstract : Decellularized extracellular matrix (dECM) derived from the target tissue is thought to augment regeneration, but limited dECM is obtained from small organs like vocal folds (VFs). VF dECM and a commercial alternative, small intestinal submucosa (SIS) possess similar proteomic content. Additionally, hydrogels from SIS and VF dECM stimulate the deposition of the ECM components at comparable levels.